THE BASICS OF SUPPLY CHAIN MANAGEMENT (Ustozlar uchun, 2025)
AbstractSupply Chain Management (SCM) is an essential discipline in today’s globalized and highly competitive business environment. It involves the integrated coordination of activities from sourcing raw materials to delivering finished products to consumers. This article provides a comprehensive overview of SCM, discussing its key components, primary objectives, critical processes, technological influences, challenges, and future trends. Understanding these elements equips businesses to optimize operations, reduce costs, manage risks, and enhance customer satisfaction effectively.